2021
DOI: 10.2174/1389201021666201117095215
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Serum Calprotectin as a New Marker in Abdominal Aortic Aneurysms – A Preliminary Report

Abstract: Background: Abdominal aortic aneurysm (AAA) remains a surgical challenge. There are many recognizable markers associated with the formation of AAA. Previous experiments carried out on animal models have shown a correlation between serum calprotectin and the occurrence of AAA. Objective: This study aimed to evaluate the level of calprotectin as a potential diagnostic biomarker in patients with diagnosed AAA. Method: The study group consisted of 75 patients aged 35–75 years who were assigned to two groups: a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For example, Hauzer et al observed increased levels of calprotectin in patients with AAA compared to controls, and interestingly, these levels were reduced after surgery. 15 They also found differences in the levels of soluble receptor for advanced glycation end products (RAGE) between the two groups, 16 but were unable to establish a correlation between both markers (calprotectin or RAGE) and aortic diameter, probably due to limited sample size. 17 In contrast, our control group comprised healthy volunteers and carotid endarterectomy patients with severe atherosclerosis, who were analyzed separately to determine whether calprotectin would be able to differentiate AAA from other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hauzer et al observed increased levels of calprotectin in patients with AAA compared to controls, and interestingly, these levels were reduced after surgery. 15 They also found differences in the levels of soluble receptor for advanced glycation end products (RAGE) between the two groups, 16 but were unable to establish a correlation between both markers (calprotectin or RAGE) and aortic diameter, probably due to limited sample size. 17 In contrast, our control group comprised healthy volunteers and carotid endarterectomy patients with severe atherosclerosis, who were analyzed separately to determine whether calprotectin would be able to differentiate AAA from other vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AAA also display an increased level of calprotectin in comparison to patients with a healthy aorta. That level decreases significantly after the removal of AAA [11,12].…”
Section: Pathogenesis Of Aaa Formationmentioning
confidence: 93%
“…Similarly, miRNA profiling produced under-expressed and overexpressed sequences suggesting the role in regulatory mechanisms [ 25 , 26 , 27 ]. Tissue factors related with inflammatory infiltrates and matrix degradation, such as pentraxin [ 28 ], galectin [ 29 ], calprotectin [ 30 , 31 ], kallikrein [ 32 ], and granzyme [ 33 ], correlate with the presence of AAA and might help in identifying patients at risk of AAA rupture ( Figure 2 ).…”
Section: Biomarkers and Compounds In Abdominal Aortic Aneurysms (Untreated Disease)mentioning
confidence: 99%